Income inequality and crime: evidence from a dynamic panel data approach - Goh, Lim Thye; Kaliappan, Shivee Ranjanee; Ishak, Suryati (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
Motivated by the inconclusive evidence from previous empirical studies on the nexus between crime and income inequality, this study investigates the effect of income inequality on crime using the dynamic panel system generalized method of moments (GMM) for the period of 1989-2012. The study also provides new evidence that sheds light on the role that institutional quality plays in moderating the relationship between income inequality and crime. The empirical results indicate that income inequality is positively associated with crime. However, better institutional quality has a negative moderating effect on the relationship between income inequality and crime. The findings of the marginal effect reveal that the effect of income inequality on crime is significant at the mean level of the institutional quality variable.